Hermeneutika Khaled Abou El Fadl - Syarifuddin Syarifuddin (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2015)
According to Abou el Fadl, authoritative hermeneutics is the only approach that is able to address the current issues of Islamic law, which are still considered discriminative. Abou el Fadl proposes a theory using hermeneutic approach as the basis analysis in addressing these issues. For him, reinterpretation of Islamic law interpretations becomes so salient in order to avoid an attitude which what Abou el Fadl calls interpretations authority. Therefore, hermeneutics which Abou el Fadl develops is oriented toward the interpretation authority of a text by negotiating the text itself, the author and the readers, as well as considering the personalities of the interpreters (readers). By using such authority theory, Abou el Fadl tries to construct the notion of authority in Islamic discourse. Regarding the concept of Islamic authority in its construction as a form of bridging the will of God, Abou el Fadl pays attention to three things, namely;